2013
DOI: 10.1080/08927014.2013.788692
|View full text |Cite
|
Sign up to set email alerts
|

Anti-biofilm activities of quercetin and tannic acid againstStaphylococcus aureus

Abstract: Staphylococcus aureus is a leading cause of nosocomial infections because of its resistance to diverse antibiotics. The formation of a biofilm is one of the mechanisms of drug resistance in S. aureus. The anti-biofilm abilities of 498 plant extracts against S. aureus were examined. Seventy-two plant extracts belonging to 59 genera and 38 families were found to significantly inhibit the formation of biofilms of S. aureus without affecting the growth of planktonic cells. The most active extract, from Alnus japon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(141 citation statements)
references
References 30 publications
9
126
3
3
Order By: Relevance
“…Briey, paper discs of 4 mm in diameter soaked with different concentrations of PJE, baicalein, quercetin and chrysin were placed on an agar plate overlaid with so agar (0.7%) that was previously inoculated with P. aeruginosa. The plate was then incubated at 37 C for 48 h. Aer the incubation, the diameter of the clear zone (mm) around the disc was measured which indicates the antibacterial sensitivity.…”
Section: Determination Of Antibacterial Susceptibilitymentioning
confidence: 99%
“…Briey, paper discs of 4 mm in diameter soaked with different concentrations of PJE, baicalein, quercetin and chrysin were placed on an agar plate overlaid with so agar (0.7%) that was previously inoculated with P. aeruginosa. The plate was then incubated at 37 C for 48 h. Aer the incubation, the diameter of the clear zone (mm) around the disc was measured which indicates the antibacterial sensitivity.…”
Section: Determination Of Antibacterial Susceptibilitymentioning
confidence: 99%
“…Free radicals damage protein and nucleic acids during the oxidative stress response. Quercetin can scavenge free radicals and downregulate the downstream signaling pathway mediated by reactive oxygen species, thereby regulating intracellular signal molecules and protecting cells from oxidative stress injury (Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The antibiofilm activity of the seed extracts against Streptococcal and Staphylococcal species may be an important tool for decrease microbial colonization on the surfaces and the epithelial mucosa which is main causes of infections by interrupting the release of the adhesion compound lipoteichoic acid from the cell surface, 24 or alteration of bacterial gene expression could be mediated the anti-biofilm action. 25 As a result concluded that the antibacterial and antibiofilm activity of Ammi majus seed due to their bioactive constituent present in it because phenolic acid, terpenes, tannin and flavonoids 10,[26][27][28][29] were found to exhibit marked antibacterial and antibiofilm activity.…”
Section: Anti-biofilm Activity Of Seed Extractsmentioning
confidence: 99%